Quantum critic: conhecimento e comunicação em transmutação físico-matemática - Guerra Filho, Willis Santiago (2017)
Just as in nature what is here characterized as quantum critic represents the infinite or instantaneous speed between phase changes, the foundation of science lies in the quantum critic of the transition from scholastic thought free from algebra to modern, fully mastered thinking through mathematical symbology. In medieval scholasticism we see a point of transmutation within a process of seeking the unification of geometry and arithmetic, or more commonly, of philosophy and science. Now we are about to hit another quantum critic, by the exponential development of technology, which is often enthusiastically referred to as a "singularity" when we need to look at the risks of programming machines to replace with immeasurable advantage its programmers, becoming autopoietic, as life, and hence perhaps compete with us, as it happens in nature. It is when the results of "technical transmutation" proliferate, giving rise to the emergence of autopoietic social systems, as described by the German sociologist Niklas Luhmann, from the notion proposed in biology of knowledge by authors such as Chilean Humberto R. Maturana, which are imposed on humans, even if it is for them a condition of possibility of their existence, for by a recursive mechanism, autologically explicable (Heinz von Foerster), positions are reversed, systems becoming a condition of social existence for us humans since we know of no other way of existing than socially. The present difficulty of communication, bordering impossibility, since it grows inexorably and exponentially in the society developed from it, like the entropy in any physical system, has been causing ever greater problems to the life that depends on it, that of us humans. Such a crisis of the systems of meaning, in order to be overcome, requires that the generalized disagreement now in force be recognized, to be reversed by a reprisal of words worn by the unceasingly contested use, so that new or renewed words may arise which is needed, to regain faith in the very possibility of communication. And this is a faith in our ability to communicate, despite the electronic prosthesis that proliferates, giving the false impression of coming to our aid, and in fact helps, but with that reinforce our fundamental disbelief in that capacity, in ourselves, since there is no god left to secure it. Stills there is the hope that inspires us such authors as Vilém Flusser, in a convergence between the arts, sciences and techniques, that could allow us to once again go beyond the limits of an improbability to remain as species, due to a "passage through the poetic" (Heidegger)